Volcanogenic Tonsteins from Bukit Asam Coalfield, South Sumatra Basin, Indonesia - Anggara, Ferian (2016)
In the Muara Enim Formation, at least 18 coal layers are found, however only five main coal seams layer in Bukit Asam coalfield e.g the A1 and A2 (Mangus) seams, B1 and B2 (Suban) seams as well as C (Petai) seams are considered economic to be mined. A major influence on the evolution of peat mires and coal formation in the Muara Enim Formation was volcanic activity during the deposition. Volcanic eruptions in the surrounding area produced ash which accumulated as claystone layers or tonsteins in the coal seams. Based on systematic field mapping, several tonsteins layers were founded and sampled in the research area, e.g. tonsteins in interseam layer of A1, A2, B1, B2 and C seam. This paper only focused on the tonstein in between B and C seam. The mineralogy of the tonsteins has been evaluated using thin section and qualitative X-ray diffraction (XRD) techniques. Tonstein in Bukit Asam coalfield, consisting mainly of kaolinite, quartz, dickite and calcite. The results suggest that these tonsteins were derived from acid volcanic ash fallout, which was subsequently altered into relatively kaolinitic rocks through hydrolysis and diagenesis in a peat-bog environment. The tonsteins in Muara Enim Formation are significance in providing distinctive horizons for stratigraphic correlation purposes